Characteristics of Ashes from the Combustion of Cow Dung Biomass - Aneta Szymajda; Grażyna Łaska; Maciej Majewski (Proceedings, 2020)
Cow dung biomass was collected from January 2019 to June 2019. The tests were carried out on the samples of ground biofuel with a fraction below 0.42 mm, subjected to incineration. The chemical composition of ashes and characteristic fusion temperatures were determined. Cow dung biomass ashes were found to contain chlorine, which can contribute to corrosive processes in boilers.